Study of abnormal haemoglobin variants using cation exchange high performance liquid chromatography (HPLC) in paediatric population of Gujarat, India - Shubhi Saxena; Richa Jain (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Haemoglobinopathies particularly β thalassemia and sickle cell anemia are the most commonly encountered single gene disorders in the India; so as in Gujarat. The data pertaining to their occurrence and prevalence in the state of Gujarat are scarce and hence it was considered worthwhile to study the burden of haemoglobinopathies in Gujarat, India. The objective of current study is to find occurrence of haemoglobinopathies in paediatric population.Materials and Methods: Analysis of blood samples of 1560 cases referred to the pathology laboratory from paediatric department for the workup of anemia or other blood related disorders was done by Bio Rad D 10 Dual program HPLC instrument.Results: Of the 1560 paediatric cases, samples analyzed on Bio Rad D 10 Dual program HPLC for haemoglobinopathies, 1003 abnormal haemoglobin variants were detected in which maximum 652 (65%) as sickle cell trait, 174 (17.3%) as sickle cell disease, 139 (13.8%) were diagnosed as β-thalassemia trait, 34 (3.3%) were diagnosed as S-β double heterozygous, 02 (0.19%) as β-thalassemia major and 01 (0.09%) as HbE trait, 01 (0.09%) as HbD trait.Conclusion: The prevalence of haemoglobinopathies among children is more commonly seen in countries with limited resources, where priority tends to be given to tackling infant and child mortality from infections and malnutrition. This study indicates that almost all the common haemoglobinopathies are prevalent in Gujarat but sickle cell trait/anemia and β thalassemia are very common.